Experiencia ganada con una “Ficha de evaluación rápida de sistemas silvopastoriles” - Colcombet, Luis (2023)
In Argentina, on one side, there is an increasing demand to start up silvopastoral systems of diverse composition and different regions and, on the other hand, a small group of professional practitioners with the sufficient knowledge to offer correct counselling, that requires a comprehensive multidimensional view, integrating the tree, forage, cattle, environment, and human aspects. The “Quick silvo-pastoral evaluation file” objective is to offer a mean to gather relevant information that offers a graphic “spider web” evaluation, that facilitates the decisions the users must make to increase their performance. To construct the file, a series of workshops integrated by professionals of the five axes before mentioned and silvopastoral experience, that have been integrated in a spreadsheet. Once the spreadsheet is loaded with a site data, it offers spider web graphs in a scale from 1 to 4 of the five evaluated dimensions that facilitates the necessary decision making and a mean to gain learnings and gather experience. The first version has been tested in real cases by persons that did not participate in the file construction, with good promising feedbacks. We propose more practitioners use it and provide feedback, to facilitate a second version we hope to mount in a cellular appliance.